The sensitivity and specificity of 99mTc-IgG radiotracer to differentiate infection lesions induced by Staphylococcus aureus and sterile inflammation lesions induced by carrageenan assay in rat’s foot - Saeed Heidari Kaydan; Alireza Doroudi; Faramarz Ahmadi; Mohammad Javad Khodayar; Mostafa Erfani (Electronic Physician, 2018)
Background: Detection and identification of infection from sterile inflammation foci has a crucial role in diagnosis and therapy of patients in clinical practice. Objective: To assess the efficiency of labeled human polyclonal immunoglobulin with technetium 99m in order to detect septic or aseptic lesions which were induced in a rat model. Methods: The freeze-dried IgG kits have been reconstituted by 99mTc. The radio conjugate yield, radiochemical impurities and stability radio complex were performed by ITLC (Instant Thin Layer Chromatography) and Gel filtration assays. Twenty adult, male NMRI (Naval Medical Research Institute) rats were randomly divided into two groups equally. Infection was induced by Staphylococcus aureus and sterile inflammation created by Carrageenan test. All lesions were created in the rat’s foot. Then radioisotope investigations were undertaken. Results: Labeling yield was approximately 98%. The radio complex showed good stability in normal saline. All affected feet could be easily visualized by imaging in qualitative study. The value of target to non-target ratio at the infection (n=10) and sterile inflammation (n=10) were 2.81±0.16 and 1.54±0.15 with p<0.007. Therefore, the radiotracer uptake at the septic lesions was significantly higher than the aseptic lesions. Conclusion: Imaging with 99mTc-IgG is highly sensitive to localized infection or inflammation foci. The increased accumulation of radiotracer at the infection versus inflammation foci may be helpful to interpret the image.